Optimasi Proses Demineralisasi Cangkang Rajungan (Portunus pelagicus) Kajian Suhu dan Waktu Demineralisasi - Martati, Erryana; Susanto, Tri; Yunianta, Yunianta; Efendi, Zohan (Jurnal Teknologi Pertanian, 2002)
The aim of the research was to  study the effect of temperature and the time exposure of deproteinization toward demineralized crab shell characteristic. This experiment was done in various temperature i.e.  650 C, 750C and 850 C and time exposure i.e. 2, 6 and 10 hours. The results showed the temperature treatment had influence toward ash content, calcium content, protein content  and the yield very significantly. The time exposure treatment had influence toward ash content, calcium content and  protein content very significantly. Interaction  both of that had influence toward calcium content only. The best treatment was selected by Multiple Attributes Methods. It was demineralizalition  at temperature 85 0C for 15 hours, The characteristics  of demineralized shell were ash content  0,277%, calcium content  0,123%,  water content  5,364 %, protein content 30,3% and the yield  13,21%. This treatment gave  mineral content and calcium content of demineralized shell   that fulfilled the chitin standard.Key words: chitin, demineralization, crab shell